Mathematical analysis of modeling stationary compressible flow of perfect gas - Fedorov, M. Yu. (Proceedings of National Aviation University (archive), 2003)
The formalization possibility of mathematical model describing one-dimensional stationary flow of compressible gas with the given constant heat flux, friction and mass forces that can perform work in the constant-area channel is considered in the paper. Analytical solution is obtained for energy equation of this flow model case